Microstrip Line Fed Fractal Monopole Antenna with Defected Ground Structure - S. Mohan Reddy, S; M. Vinod Kumar, M; Sanjay, B; Aruna Kumari, K; V. S. Padma Rao, G (International Journal of Engineering and Technology, 2018)
This paper presents a wideband polarized antenna that is designed and analyzed for the cellular communication applications. The proposed antenna is designed with the coplanar wave guide feeding (CPW) by using the RT/ duroid 5880 material with a dielectric constant 2.2. It is observed that in the proposed model the return loss is -21.40dB for ungrounded CPW where as for the grounded CPW the loss is reduced to -39.13dB. The gain for the ungrounded CPW fed antenna is 2.95 dB and is enhanced to 3.2dB with Â grounded CPW structure. It is observed that there is an improvement in the bandwidth upto 6.03 GhZ for grounded CPW when Â DGS is applied. The antenna designing and simulation is done using ANSOFT HFSS software.Â Â